Perdagangan tukar barang Malaysia-Indonesia (Tawau): Potensi dan cabaran - Ramli Dollah; Ahmad Mosfi Mohamad (University of Malaya, 2007)
The Malaysia-Indonesia relationship has been well-formed with various activities such as trade, culture (race), migration and others. However, this relationship has changed little, moreover with several issues that happened recently. On the contrary, less attention is given on the positive relationship of the two countries. Thus, this study will try to show the positive relationship, focusing the discussion on barter trade between Malaysia (Tawau) and Indonesia by looking at Sabah (Tawau) as trade centre with Nunukan, Tarakan and others in Indonesia.